Comparación de los modelos formativo, reflexivo y de antecedentes de evaluación estudiantil del servicio de docencia - Valdivieso Taborga; Carlos Eduardo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– A comparative analysis between three measurement models (with formative, reflective, and antecedents approach) has been conducted to measure the dimensions of the teaching service quality. Previously valid and reliable instruments have been designed to measure the service quality and related constructs. An exploratory study has been performed to obtain content validity. Additionally, both exploratory and confirmatory factor analysis (EFA and CFA, respectively) have been conducted to obtain the appropriate dimensional structure and relevant items. Using structural equations modeling (MEC) has been found that the antecedent model, although it has the same predictive power, has better fit indices than reflective and formative models.
Keywords: M39; I23; 330; teaching service quality; perceived value; student satisfaction; behavioral intentions; structural models; formative and reflective approach